PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS KONTEKSTUAL DISERTAI CERGAM MATERI LISTRIK DINAMIS SMA KELAS X - Desy Nurdiasari; Sudarti Sudarti (FKIP Universitas Jember, 2017)
The purposes of this research are to know the validity of physics learning module contextual based with characterized stories and the efektiveness of the modul. This type of research is R and D which is development by Borg and Gall (1976). The result of the research was a physics learning modul contextual based with characterized stories which was worthy to use after being validized. The first validity step was doing expert validity. The result of it was 80,86% and can be categorized as valid, or can be used with revision. The second validity step was user validity, the result it was 81,33% and can be categorized as very valid or can be used without revision. The last step was audience validity based on the result of audience vallidity , it was gotten 81,08% which said the efectivity of the modul. The result from the audience validity can be categorized as very efective, and worthy to use in teaching and learning process. Based on the result of the research, it can be concluded that physics learning module contextual based with characterized stories can use as the interesting teaching materials.